Zjedz lub zostań zjedzony. Miasto Macunaímy - Rojek, Patrycja (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2013)
Eat or Be Eaten. The City of Macunaíma Macunaíma, the trickster-hero from old Amerindian legends, was in the 1960s an icon of the Brazilian Cinema Novo – a new wave film movement that was a response by artists to class and racial disparities. Joaquim Pedro de Andrade, the director of Macunaíma (1969), moves the eponymous hero out of his jungle and puts him into the modern, mechanized and restless big city. Not only are social problems strongly emphasized in the film – equally important is here the aspect of myth itself. Macunaíma enters the new world as a real old-time god who sees the city as his opponent. During his battle – full of trickery and plotting – it emerges that the difference between the Amazonian jungle and the concrete jungle are barely visible.